Test Of Hundreds Established Hybrid Rice Seed Derivatives P-05 And Quantity Of Cemeti Inbrid Rice Derivatives On Product Quality And Quantity - Irfanji Fanji; Suharno Suharno; RR. Siti Astuti (Politeknik Pertanian Negeri Samarinda, 2022)
This study aims to determine the combination of treatment of ratoon derived from F1 rice seeds (Hybrid) of Mapan P-05 and ratoon derived from rice seeds (Inbred) whip with various spacings on the quality and quantity of which yield is the best and to know the interaction factors of ratoon derived from Mapan hybrid rice seeds. P-05 and whip inbred rice were the best in terms of yield quality and quantity. Held from December 2021 to June 2022. And planting of ratoons was carried out on November 14, 2021-March 31, 2022. This research was carried out in Sumberharjo Village, Prambanan District, Sleman Regency, Special Region of Yogyakarta. This study used a Completely Randomized Block Design (RAKL) factorial. The first factor is ratoon rice with two varieties and the second factor is the treatment of various spacings of 20x20;25x25;30x30 cm. Data analysis used ANOVA with a level of 5% and 1%, if it had a significant effect, it was followed by a significant difference test (DMRT) with a level of 5%. The results showed that the hybrid variety treatment always showed higher yield quality and quantity than the whip inbred with spacing treatment. 20x20 cm and followed by a spacing of 25x25 cm and 30x30 cm from the Inbred cemeti variety. The combination of hybrid varieties treatment with 20x20 cm spacing gave the heaviest results on the average weight of dry grain harvested per plot, weight of dry grain storage per plot, weight of 1000 grains of grain, weight of dry grain harvested.